On Conformal Metrics with Constant $Q$-Curvature (Analysis in Theory and Applications, 2019)
We review some recent results in the literature concerning existence of conformal metrics with constant $Q$-curvature. The problem is rather similar to the classical Yamabe problem: however it is characterized by a fourth-order operator that might lack in general a maximum principle. For several years existence of geometrically admissible solutions was known only in particular cases. Recently, there has been instead progress in this direction for some general classes of conformal metrics.